Pengaruh Persepsi Risiko, Kepercayaan Dan Keamanan Terhadap Minat Menggunakan BSI (Bank Syariah Indonesia) Mobile - Wida Utami; Ika Dina Rofika; Trisma Kamelia; Yulia Budiarti; Tasnim Mushlihah; Hanifah Aminin; Rizka Awaliya Nur Azizah; Niken Septiani (Academica: Journal of Multidisciplinary Studies, 2023)
This study aims to examine the interest in using BSI Mobile in terms of perception, trust, and security risks as independent variables. This research applies a quantitative method and involves 100 respondents using BSI Mobile. The research data was obtained by distributing questionnaires online. Processing research data using multiple linear regression analysis in SPSS 23. The results of the study prove that the perceived risk variable (X1) does not affect interest in using mobile BSI with a t-count value of 0.362 < t-table value of 1.984 and a significance value of 0.718 > 0.05. The trust variable (X2) does not affect interest in using BSI Mobile with a t-count value of 1.796 < t-table value of 1.984 and a significance value of 0.080 > 0.05. Security has a positive effect on interest in using BSI Mobile with a t-count value of 6.676 > t-table value of 1.984 and a significance value of 0.00 <0.05. The implication of this research states that security is a factor that greatly influences interest in using BSI Mobile.